Assessing the Performance of Dompoase Wastewater Treatment Plant and Its Effect on Water Quality of the Oda River in Kumasi - Abuenyi, Bernard (2014)
A Thesis submitted to the Department of Theoretical and Applied Biology Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science in Environmental Science, November.